2014
DOI: 10.1108/jsbed-02-2014-0025
|View full text |Cite
|
Sign up to set email alerts
|

How small family-owned businesses may compete with retail superstores

Abstract: Purpose-The purpose of this paper is to explore the "perceptive concordance"-the proximity of perceptions of the business-between key managers and customers of two small family-owned and managed businesses ("FBs") and two larger non-FBs in Cagliari, Italy as a preliminary basis for understanding how small retail businesses that are typically family owned have continued to compete and thrive in many Western European cities. Design/methodology/approach-The authors asked how small FBs have been able to compete in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Family-owned firms, here defined as those businesses fully owned and managed by members of the founding family, with the clear intention to pass the firm to their offspring and perceive the business to be permeated by family beliefs and values (Aronoff, 2004), seem to be in a privileged position to manage quality. This advantaged situation derives from several family business features, like as the only characters and resources (Danes et al, 2008), the values (Aronoff, 2004), the innate tension toward the excellence (Vallejo, 2009), the role of the owner (Arsi c et al, 2018) and the ability to build long-lasting relationships with customers (Dess ı and Floris, 2010;Dess ı et al, 2014). For these reasons, family businesses are a suitable scenario to investigate how quality is enhanced and how TQM philosophy embraces the entire family firm strategy.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Family-owned firms, here defined as those businesses fully owned and managed by members of the founding family, with the clear intention to pass the firm to their offspring and perceive the business to be permeated by family beliefs and values (Aronoff, 2004), seem to be in a privileged position to manage quality. This advantaged situation derives from several family business features, like as the only characters and resources (Danes et al, 2008), the values (Aronoff, 2004), the innate tension toward the excellence (Vallejo, 2009), the role of the owner (Arsi c et al, 2018) and the ability to build long-lasting relationships with customers (Dess ı and Floris, 2010;Dess ı et al, 2014). For these reasons, family businesses are a suitable scenario to investigate how quality is enhanced and how TQM philosophy embraces the entire family firm strategy.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…, 2008), the values (Aronoff, 2004), the innate tension toward the excellence (Vallejo, 2009), the role of the owner (Arsić et al. , 2018) and the ability to build long-lasting relationships with customers (Dessì and Floris, 2010; Dessì et al. , 2014).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Recently, social media have become increasingly relevant for SMEs (Meske & Stieglitz, 2013) because of the opportunities they offer in enhancing communication with customers (Castronovo & Huang, 2012), improving interaction with suppliers (Michaelidou, Siamagka, & Christodoulides, 2011), reinforcing brand reputation (Wang et al, 2016), adopting innovation (Muninger, Hammedi, & Mahr, 2019) and sharing knowledge and perception (Kwon, Mai, & Peng, 2019). However, even if SMEs are aware of the potential that derives from social media adoption and conscious of their ability to create face-to-face, long-lasting relationships with customers (Cabras et al, 2009;Cooper et al, 2005;Dessì & Floris, 2010;Dessi et al, 2014;Soltani et al, 2018), they undervalue the extraordinary power social media can have in terms of customer interactions (Guha et al, 2018). In other words, SMEs embody a spontaneous ability in managing customer relations; conversely, they do not fully appreciate the pervasive role of technological opportunities in improving customer relations through social media tools (Rageh et al, 2013;Zontanos & Anderson, 2004).…”
Section: Social Media In Smesmentioning
confidence: 99%
“…This pervasive phenomenon is becoming an 'integral part of everyday life' (McCann & Barlow, 2015, p. 273) and has also affected firms' domains (Hawkins & Vel, 2013) of large enterprises and small and medium enterprises (SMEs) because it is a relatively quick and low-cost means of relating with customers (Fischer & Reuber, 2011). However, despite the fact that SMEs appear to be unique in creating long-lasting relationships with customers (Cabras, Dessi, & Floris, 2009;Cooper, Upton, & Seaman, 2005;Dessì & Floris, 2010;Dessi, Ng, Floris, & Cabras, 2014;Soltani, Zareie, Milani, & Navimipour, 2018), they tend to avoid the use of social media, which undervalues their power in influencing customers, valorising specific brands or products and emphasising positive reviews of services (Guha, Harrigan, & Soutar, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile Turner and Endres (2017), found that only one-third of small business start-up survive more than ten years. Therefore, in an effort to curb the increasing number of small business failure, many scholars and experts suggested to the owner-managers of small businesses to practice strategic management concept in their daily operation, particularly by developing an effective business strategy (Nadim & Lussier, 2002and Garrigós-Simón, Marqués, & Narangajavana, 2005, Zakaria, 2010, Dessi, Ng, Floris, & Cabras, 2014 Meanwhile, from a Resource Base View (RBV) perspective, this school of thought suggested to the firm to combine their resources and capabilities together if they want to achieve above average return and competitive advantages (Peteraf, 1993, Andersén, 2011, and Crema, Verbano, & Venturini,2014. They claimed that internal resources and distinctive competencies owned by the firms are another factor that contributes to the success of the firm and one of the area that can be focused on is marketing function (Hitt, Duane, & Hoskisson, 2001, O'Cass, Ngo, & Siahtiri, 2012, and Conant & White, 1999.…”
Section: Introductionmentioning
confidence: 99%